Murder on Brittany shores : a mystery - Bannalec, Jean-Luc, 1966- (Minotaur Books, 2016)
"Ten miles off the coast of Brittany lie the fabled Glenan Islands. Boasting sparkling white sands and crystal clear waters, they seem perfectly idyllic, until one day in May three bodies wash up on shore. At first glance the deaths appear accidental, but as the identities of the victims comes to light, cantankerous Commisaire Dupin is pulled back into action for a case of what seems to be cold-blooded murder. Ever viewed as an outsider in a region full of myths and traditions, Dupin finds himself drawn once more deep into the history of the land. To get to the bottom of the case, Dupin must tangle with treasure hunters, militant marine biologists, and dangerous divers. The investigation leads him deep into the perilous, beautiful world of Brittany, as he discovers that there's more to the picturesque islands than meets the eye. Steeped in the enchanting atmosphere of Brittany, peppered with wry humor, and full of delicious local food, this superbly plotted mystery is perfect for fans of Martin Walker and G.M. Malliet"--